Clinical Utility of Serum Cystatin C in Predicting Coronary Artery Disease in Patients Without Chronic Kidney Disease. Issue 3 (29th January 2014) - Dandana, Azza; Gammoudi, Imen; Chalghoum, Abdelkader; Chahed, Hinda; Addad, Faouzi; Ferchichi, Salima; Miled, Abdelhedi
<x xml:space="preserve">Abstract</x> Background Cystatin C has been proposed as a novel marker of renal function and predictor of cardiovascular risk. The aim of this study was to investigate the role of cystatin C level as a predictor of cardiovascular events in patients with coronary artery disease (CAD). Methods Three hundred and five coronary artery patients were included in this study. Serum cystatin C levels, high‐sensitive C‐reactive protein (hs‐CRP), and oxidative stress were measured. Estimated glomerular filtration rate (eGFR) and the CAD severity score were calculated. Results Cystatin C was correlated with the CAD severity score (r = 0.631, P < 0.0001) and was significantly elevated in the CAD severity score >50. Every 0.1 mg/l increase in cystatin C, 2 mg/l increase in hs‐CRP, 0.2 mmol/l decrease in high‐density lipoprotein cholesterol, 13.7 ml/min decrease in eGFR, and 1.51 μmol/l increase in homocysteine caused a 34, 12, 5, and 22% increase in the risk of having CAD, respectively. Conclusion Cystatin C could be a useful laboratory biochemical marker in predicting the severity of CAD. Cystatin C is associated with biochemical atherosclerosis markers such as CRP and homocysteine.